2017
DOI: 10.1016/j.astropartphys.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Primordial gravitational waves in running vacuum cosmologies

Abstract: We investigate the cosmological production of gravitational waves in a nonsingular flat cosmology powered by a "running vacuum" energy density described by ρ Λ ≡ ρ Λ (H), a phenomenological expression potentially linked with the renormalization group approach in quantum field theory in curved spacetimes. The model can be interpreted as a particular case of the class recently discussed by Perico et al. (Phys. Rev. D 88, 063531, 2013) which is termed complete in the sense that the cosmic evolution occurs betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…This is one of the main aims of the present paper. Recent similar studies have appear in the literature Similar recent studies have appeared in the literature [35].…”
Section: Introductionsupporting
confidence: 82%
“…This is one of the main aims of the present paper. Recent similar studies have appear in the literature Similar recent studies have appeared in the literature [35].…”
Section: Introductionsupporting
confidence: 82%
“…Using the Einstein equations and the above solutions we can obtain the corresponding energy densities: 34) withρ I ≡ 3H 2 I /8πG. These expressions reproduce the energy densities for the primeval de Sitter and radiation dominated epochs, for details see Figure 5.1.…”
Section: From the Early De Sitter Stage To The ω-Dominated Phasementioning
confidence: 78%
“…It is found that the spectrum is very similar to the one predicted by the cosmic concordance model plus inflation except for high frequencies. The first results of this part have been submitted for publication [34].…”
Section: Outline Of the Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…• the effects of expansion on the GW group and phase velocities [409,410] • mathematical aspects and exact solutions [411][412][413][414][415] • quantum and thermodynamic properties of GWs [124,416] • general properties [414,417,418] • nonlinear effects [419] • properties of the GW energy momentum tensor [420] • collision of GWs with electromagnetic waves [421] • evolution of GWs in gravitational plasma [422] Even though these studies have properly taken into account the expansion of the background metric, they have not taken into account the effects of the gravitational field of mass distributions on the evolution of the GWs. Such a gravitational field combined with the expanding background may induce new observable effects on the spectrum of propagating gravitational waves affecting the amplitude and the frequency of such waves, due to gravitational time delay [423].…”
Section: Effects On Gravitational Waves In An Expanding Universementioning
confidence: 99%